Innovation in the Field of Learning: Deep Learning Approach and Its Application in Learning at Hayat School Bandung City - Nasir, Tatang Muh; Rohima, Yulia Kuraesin Ila; Sabarudin, Mohammad; Yasir, Muhamad; Supiana, Supiana; Zaqiah, Qiqi Yuliati (Al Ulya: Jurnal Pendidikan Islam, 2025)
The rapid advancement of technology in the digital era demands that the field of education adapt by creating learning models that are contextual, personalized, and meaningful. One relevant approach to addressing this challenge is Deep Learning, which integrates artificial intelligence with experiential, pedagogy-based methods. This study aims to examine the implementation of the Deep Learning approach in the learning process at Hayat School Bandung SCM (School of Creative Minds) and its impact on the development of 21st-century competencies and student character. The research employs a descriptive qualitative method using techniques such as observation, documentation, and interviews with educators, students, and parents, alongside an analysis of the curriculum and supporting facilities at Hayat School. Data were analyzed inductively to uncover the meanings and transformative practices within the learning process. The findings reveal that the Deep Learning approach is applied through contextual learning, active reflection, meaningful discussions, project-based learning (PjBL), and a personalized curriculum. Teachers, referred to as "Kakak Fasil" (Facilitator Siblings), serve as facilitators who encourage student exploration and self-awareness. This approach proves effective in enhancing critical thinking skills, social empathy, and student spirituality. The discussion highlights that a tauhidullah-based curriculum and inclusive learning facilities support the success of this approach. In conclusion, Deep Learning at Hayat School not only improves academic quality but also shapes holistic individuals who are prepared to face future challenges with a strong internalization of Islamic values.